Editor’s Note: Garuba, I. O. (2019). The Ageing Poet and Death Anxiety: Art as Existential Therapy in John Pepper Clark’s Of Sleep and Old Age. English Studies at NBU, 5(2), 268-283. DOI 10.33919/esnbu.19.2.5 - Bogdanov, Stanislav (English Studies at NBU, 2020)
For the benefit of our readers, we are publishing this Editor’s Note to assert that the version published on 30 December 2019 in English Studies at NBU, Volume 5, Issue 2, 2019, is the authoritative and only version of record.